Human Resource Quality Analysis On Customer Satisfaction At Care Inn Hotel - Maria Laura Irwantari; Koen Irianto Uripan; Setio Kuncoro; Siti Nur Soleha; Ahmad Zainuddin (International Humanity Advance, Business & Sciences, 2026)
This study aims to analyze the effect of the quality of human resources services (workers) on customer satisfaction at the hotel Care Inn Merauke, taking into account disconfirmation as a mediation variable. Using a quantitative approach with survey methods, this study involved 382 respondents who were hotel customers during the period from January to May 2025. The research Model refers to SERVQUAL, which consists of five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The results of the analysis using Partial Least Squares-Structural Equation Modeling (PLS-SEM) showed that the model built has a high validity and reliability, with the value of R2 for customer satisfaction of 75.7%. The findings showed that the dimensions of Empathy, Reliability, and Assurance have a direct and significant effect on customer satisfaction, while Tangibles have a small effect, and Responsiveness is not significant. Disconfirmation acts as a partial mediator in the relationship between the quality of Human Resource Services (workers) and customer satisfaction, with a significant influence of Empathy, Reliability, and Assurance on disconfirmation. These findings indicate that customer satisfaction at Care Inn Merauke Hotel is more influenced by relational experience and effectiveness of services that are able to meet customer expectations than physical aspects or responsiveness. The study concludes that customer satisfaction improvement strategies should emphasize the management of interpersonal expectations and experiences, as well as recommendations for further research in the context of hospitality in non-metropolitan areas. The findings are expected to provide practical insights for hotel management and academic contributions in the development of Service theory.